1988
DOI: 10.1021/bi00408a056
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity labeling of Escherichia coli RNA polymerase/poly[d(A-T)] transcription complexes by nascent RNA

Abstract: To elucidate the molecular interactions during transcription by Escherichia coli RNA polymerase, we have performed a quantitative analysis of the photoaffinity labeling produced by an aryl azide positioned at the leading (5') end of the nascent RNA. Macromolecular contacts on the path of RNA across the transcription complex containing the template poly[d(A-T)] are observed as a function of the length of the transcript. Quantitative analysis provides the percent yield of photoaffinity labeling in the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…and o were labeled [9]. However, no DNA binding can be observed for the B subunit alone, consistent with our results from Southwestern assays, but sub-assembled a&3 complexes bind to limited sites on DNA [ 13,14,24]. The observation that most of the known mutations responsible for rifampicin resistance and streptolydigin resistance resides in a region of the E. colip subunit corresponding to nucleic acid-binding region 1 points to a functional importance of this region.…”
Section: Discussionsupporting
confidence: 80%
“…and o were labeled [9]. However, no DNA binding can be observed for the B subunit alone, consistent with our results from Southwestern assays, but sub-assembled a&3 complexes bind to limited sites on DNA [ 13,14,24]. The observation that most of the known mutations responsible for rifampicin resistance and streptolydigin resistance resides in a region of the E. colip subunit corresponding to nucleic acid-binding region 1 points to a functional importance of this region.…”
Section: Discussionsupporting
confidence: 80%
“…Apart from its involvement in the formation of the RNA polymerase core the role of the a subunit has not been defined. Data obtained from cross-linking studies have not provided evidence for contacts between a and DNA (Chenchick et al, 1981;Park et al, 1982) or between a and the nascent transcript (Bernhard & Meares, 1986;Stackhouse & Meares, 1988). The anti-a monoclonal antibody, mAb 126C6, used in this study has been shown to bind to an epitope that is available on both of the a subunits in the RNA polymerase core and holoenzyme (Riftina et al, 1989).…”
Section: Discussionmentioning
confidence: 79%
“…In parallel approaches using chemical or photochemical probes attached to oligonucleotide primers for RNA polymerase, Grachev et al (1989) and Stackhouse andMeares (1988, 1989) have very elegantly probed the contacts between the growing nascent RNA chain and the E. coli RNA polymerase. Similar experiments with yeast RNA polymerase have also been performed (Riva et ul., 1987).…”
Section: Oligonucleotide Probesmentioning
confidence: 99%